2014
DOI: 10.1093/ageing/afu165
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength, ageing and mortality in rural Africa

Abstract: Background: muscle strength measured as handgrip strength declines with increasing age and predicts mortality. While handgrip strength is determined by lifestyle through nutrition and physical activity, it has almost exclusively been studied in western populations with a sedentary lifestyle. This study aims to investigate the relation between handgrip strength, ageing and mortality in a population characterised by a predominance of malnutrition and manual labour.Design: a population-based longitudinal study.Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 30 publications
6
43
0
Order By: Relevance
“…[9][10][11][12][13] Our finding of similar associations between grip strength and all-cause mortality across age groups is in line with the few previous reports which have been able to stratify analyses by age. 14-16 19 22 23 Our finding of an equally strong inverse association between grip strength and all-cause mortality in men and women is also consistent with findings in other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[9][10][11][12][13] Our finding of similar associations between grip strength and all-cause mortality across age groups is in line with the few previous reports which have been able to stratify analyses by age. 14-16 19 22 23 Our finding of an equally strong inverse association between grip strength and all-cause mortality in men and women is also consistent with findings in other studies.…”
Section: Discussionsupporting
confidence: 90%
“…9 Since the publication of this review, subsequent studies have continued to find that weaker grip strength is associated with increased all-cause mortality rates in a range of settings. [10][11][12][13] Most studies of grip strength in middle and old age have investigated associations with all-cause mortality, and studies that have examined causespecific mortality are not as numerous. [14][15][16][17][18][19] Furthermore, often such studies are only powered to investigate broad groups of causes of death such as cardiovascular disease (CVD) and cancer, and have not been able to look at additional causes such as ischaemic heart disease (IHD), respiratory diseases and external causes.…”
Section: Introductionmentioning
confidence: 99%
“…States) and LMICs. For example, compared to age-and BMI-matched older people in high-income countries, it has been reported that women but not men in LMICs have higher handgrip strength (Koopman et al, 2014). Unlike Western populations, most old age people and in particular women in low-income countries engage in lifelong physical exercise (Koopman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related decline in handgrip strength (HGS) is a simple and powerful predictor of future disability (Rantanen et al 1999;Giampaoli et al 1999) and mortality (Rantanen et al 2000;Metter et al 2002;Al Snib et al 2002;Newman et al 2006;Sasaki et al 2007;Ruiz et al 2008;Koopman et al 2015). Recently, Leong and Teo (2015) investigated the association between HGS, cause-specific mortality, and incident disease using a large sample (139,691 participants) from 17 different countries.…”
Section: Introductionmentioning
confidence: 99%